Skin Diseases Discover based On Artificial Intelligence - Khaled Khalifa SAID; CHIBANI Belgacem RHAIMI; Salem Asseed Alatresh (Bani Waleed University Journal of Humanities and Applied Sciences, 2024)
Medical research is increasingly focusing on artificial intelligence (AI). The field of dermatology is using this contemporary instrument more and more often. In the practice of healthcare, this will undoubtedly influence and contribute to the future for both patients and providers. It's critical to comprehend how this technology will develop. The application of AI to dermatology is a relatively new development. Because skin diseases involve a wealth of clinical data and images, dermatologists must comprehend AI concepts. This might be the big thing when it comes to using AI in medicine. Studies on skin conditions like onychomycosis, psoriasis, atopic dermatitis, and skin cancer have already been conducted using artificial intelligence. An outline of AI and recent advancements in dermatology is given in this paper. It is crucial to look into both its potential for the future and its current uses. Professionals' attitudes regarding artificial intelligence should be examined because it is recognized as a crucial objective that must be met.